The Gambia : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver and Modification of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the First Review Under the Poverty Reduction and Growth Facility (PRGF). Overall performance under the program has been strong. All but one of the quantitative performance criteria and indicative targets were met. Fiscal performance has been impressive, reflecting higher-than-projected revenues and strengthened expenditure control. However, two structural performance criteria were not observed. The medium-term macroeconomic framework underlying the program has been modified slightly. Maintaining fiscal discipline remains key to lowering domestic public debt and protecting poverty-reducing expenditures.